IMPLEMENTASI MODEL PEMBELAJARAN PAKEM (PARTISIPATIF, AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V SD NEGERI 05 SEPOTONG KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - kurniaman, otang; ', Umar; ', lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems that occurred in the fifth grade students of SD Negeri 05 Piece Small Siak District of Bengkalis is low learning achievement of students in math in the first half. Some of the factors that lead students to master difficult subjects Changing common fraction into a decimal, among others, came and teachers less than the maximum in the use of instructional media other causes originate and students who are still a lot of play in the learning process. This research aims to improve students' mathematics learning outcomes. Results of this study was obtained from observations of the activities of teachers and students during the learning process and student achievement test. This research is a form of action research consisted of two cycles. An increase in activity of teachers and students at each cycle using PAKEM Learning Implementation Model. In the first cycle replicates the average value replications 69.17, while the second cycle of the average value increased by 11:16 points to 80.33 with completeness 30 students (100%), and students who do not complete 0 (0%). From the results of this study concluded that PAKEM Learning Implementation Model (Participatory, Active, Creative, Effective, and Fun) can Improve Learning Outcomes Elementary School Math Class V 05 Small Piece Siak District of BengkalisKeywords : Application of Learning Model AJEL, Mathematics Learning utcomes and PTK